1999
DOI: 10.1161/01.cir.99.21.2750
|View full text |Cite
|
Sign up to set email alerts
|

Dilated Cardiomyopathy Is Associated With Significant Changes in Collagen Type I/III ratio

Abstract: Differential increase of Col I and Col III leads to an increased Col I/Col III ratio in DCM myocardium. Because Col I provides substantial tensile strength and stiffness, this may contribute to systolic and in particular diastolic dysfunction in DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
193
4
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 310 publications
(214 citation statements)
references
References 24 publications
9
193
4
8
Order By: Relevance
“…Considering that all patients presented systolic dysfunction, we demonstrated that with more type I collagen, which is associated with strength and stiffness, the left ventricular ejection fraction is worse. On the other hand, a previous study of dilated cardiomyopathy with left ventricular ejection fraction lower than 50% presented increased I/III ratio, and related this finding to systolic and diastolic dysfunction (38). What seems to be contradictory, at first analysis, is that the normal myocardium had a lower proportion of collagen III/I mRNA compared with that in the dilated cardiomyopathy groups.…”
Section: Collagen Type Iii/i Expression Ratiomentioning
confidence: 86%
“…Considering that all patients presented systolic dysfunction, we demonstrated that with more type I collagen, which is associated with strength and stiffness, the left ventricular ejection fraction is worse. On the other hand, a previous study of dilated cardiomyopathy with left ventricular ejection fraction lower than 50% presented increased I/III ratio, and related this finding to systolic and diastolic dysfunction (38). What seems to be contradictory, at first analysis, is that the normal myocardium had a lower proportion of collagen III/I mRNA compared with that in the dilated cardiomyopathy groups.…”
Section: Collagen Type Iii/i Expression Ratiomentioning
confidence: 86%
“…Sirius Red staining Total collagen content of the Sirius Red (Polyscience, Warrington, PA, USA) stained sections was measured under circularly polarised light according to previously published methods [18] and quantified by digital image analysis as described in detail elsewhere [19]. Perivascular fibrosis was not measured.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas collagen III forms an elastic network storing kinetic energy as elastic recoil, collagen I represents a stiff fibrillar protein providing tensile strength. 25,26 Only the collagen I and not the collagen III promoter is studded with SP-1-binding sites. Therefore, the differential increase of collagen I over collagen III in galectin-3-infused animals could be explained by the possible differences in the molecular makeup of their promoter sites.…”
Section: Significance Of Interstitial Fibrosis and Collagen I Productmentioning
confidence: 99%